A novel diffusion–biphasic hydrolysis coupled kinetic model for dilute sulfuric acid pretreatment of corn stover. (February 2015) - Chen, Longjian; Zhang, Haiyan; Li, Junbao; Lu, Minsheng; Guo, Xiaomiao; Han, Lujia
Graphical abstract: Highlights: Dilute acid pretreatment of corn stover at moderate temperatures was investigated. A novel diffusion–biphasic hydrolysis coupled kinetic model was proposed. The contributions to xylose yield were quantitatively analyzed. The impact of particle size and acid concentration on xylose yield was investigated. Abstract: Kinetic experiments on the dilute sulfuric acid pretreatment of corn stover were performed. A high xylan removal and a low inhibitor concentration were achieved by acid pretreatment. A novel diffusion–hydrolysis coupled kinetic model was proposed. The contribution to the xylose yield was analyzed by the kinetic model. Compared with the inhibitor furfural negatively affecting xylose yield, the fast and slow-hydrolyzing xylan significantly contributed to the xylose yield, however, their dominant roles were dependent on reaction temperature and time. The impact of particle size and acid concentration on the xylose yield were also investigated. The diffusion process may significantly influence the hydrolysis of large particles. Increasing the acid concentration from 0.15 M to 0.30 M significantly improved the xylose yield, whereas the extent of improvement decreased to near-quantitative when further increasing acid loading. These findings shed some light on the mechanism for dilute sulfuric acid hydrolysis of corn stover.